“HANTU” DERRIDA DAN BERHALA KONTEMPORER - Saiful Mustofa (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
Deconstruction is a term identically to the Jacques Derrida’s figure. As one of postmodernsime-post-structuralism figure, he loudly challenges the logocentrism metaphysics of presence, included in the tradition of Semitic religions. This paper—using Derrida’s deconstruction approach—wants to look at the phenomenon of the denial of religious reasoning that has recently occurred in Indonesia. More precisely the phenomenon of “berhala kontemporer”. “Berhala kontemporer” is the attitude of the single truth and condemns the possibility of another truth. The logic used is the binary-opposition; iam right and others are wrong. As if the others were not given the opportunity to simply ask, or digest speech and writing because there was absolutely no room for the others.The author concludes that Derrida’s thinking is still contextually applied in the present era, even as long as there are people who are trapped in rigid logocentrism then deconstruction will never die.